Application of a Biomimetic Sensor Based on Iron Phthalocyanine Chloride: 4-Methylbenzylidene-Camphor Detection - Boni, Ana Carolina [UNESP]; Sotomayor, Maria Del Pilar Taboada [UNESP]; Lanza, Marcos R. V.; Tanaka, Sonia Maria C. N.; Tanaka, Auro A. (Soc Brasileira Quimica, 2010)
The construction and application of a biomimetic sensor for determination of 4-methylbenzylidene camphor (4-MBC), an ultraviolet (UV) radiation protector, are described. The sensor was prepared by modifying a carbon paste electrode with iron(III) phthalocyanine chloride (FePcCl). Amperometric measurements carried out with the sensor under an applied potential of 0.0 V vs. Ag vertical bar AgCl in a mixture of tetrahydrofuran and 0.1 mol L(-1) H(2)SO(4) solution (30:70 volume ratio) showed a linear response range from 1.8x10(-4) to 9.0x10(-4) mol L(-1). A detailed selectivity investigation for other nine UV filters was also performed. A sensor response mechanism was proposed and the results for 4-MBC quantification in commercial sunscreens and in water from swimming pools and rivers are presented.
Keywords: iron phthalocyanine; amperometric sensor; methylbenzylidene camphor